Diversity and ethnobotany of useful plants in Bandar Pusaka, Aceh Tamiang District, Indonesia - Zidni Ilman Navia; Adi Bejo Suwardi; Nuraini, Nuraini; Adnan, Adnan; Baihaqi, Baihaqi; Muhammad Yakob; Parlindungan Lubis; Chairul, Chairul (Ethnobotany Research and Applications, 2024)
Background: Plants, both wild and cultivated, contribute significantly to global food security and have a considerable impact on human health and well-being by delivering various ecosystem services. However, modernization and urbanization keep altering human lifestyles, resulting in an erosion of traditional knowledge concerning the use of plants for various purposes. This study aimed to investigate the diversity of useful plant species and their utilization by local people in Bandar Pusaka, Aceh Tamiang District, Indonesia. Methods: The ethnobotanical study was carried out in ten villages, in the Bandar Pusaka subdistrict, i.e. Pengidam, Bengkelang, Batu Bedulang, Babo, Perupuk, Serba, Pantai Cempa, Rantau Bintang, Aras Sembilan, and Blang Kandis villages. The ethnobotanical survey was carried out from July to August 2023 and included 306 randomly selected informants. The ethnobotanical investigation uses semi-structured questionnaires to gather information on the traditional knowledge of useful plants. Plant specimens were collected and identified in Universitas Samudra. Results: A total of 2,088 individual plants representing 276 species and 81 families were recorded in the study areas. In terms of frequency of citation, 121 taxa were cited by 75% or more of the interviewed people, and 9 taxa were very rarely cited. Musa x paradisiaca L., Mangifera indica L., Cocos nucifera L., Durio zibethinus L., Garcinia mangostana L., Curcuma longa L., Kaempferia galanga L., Zingiber officinale Roscoe, Annona muricata L., and Ananas comosus (L.) Merr. are the ten most cited useful plants in the study area. A total of 14 use categories delivered by plants were most commonly for medicine (111 species), ornament (100), food (96), fodder (30), ritual (14), beverages (13), building materials (11), fuelwood (9), agricultural tools, fencing, and herbicide (6 each), handicraft (4), and shade plant (2). Indigenous knowledge of useful plants was significantly associated with villages, age groups, and educational levels. Conclusions: Bandar Pusaka sub-district has a diverse range of useful plants, but only a small proportion has been used by local people, particularly wild plants. Promotion and domestication of useful plants should be a primary concern in the Bandar Pusaka sub-district to take advantage of their nutritional value and potential economic value. Moreover, enhancing local peoples’ abilities and expertise in recognizing, gathering, and preparing various useful plants is critical, since, in addition to promoting their household income, it may contribute to sustaining biodiversity and traditional knowledge. Keywords: Biodiversity; ecosystem services; indigenous knowledge; Aceh Tamiang Abstrak Latar Belakang: Tumbuhan, baik liar maupun budidaya, memberikan kontribusi signifikan terhadap ketahanan pangan global dan mempunyai dampak besar terhadap kesehatan dan kesejahteraan manusia melalui penyediaan berbagai jasa ekosistem. Meskipun demikian, modernisasi dan urbanisasi telah mengubah gaya hidup manusia yang mengakibatkan terkikisnya pengetahuan tradisional terkait pemanfaatan tumbuhan untuk berbagai keperluan. Penelitian ini bertujuan untuk mengetahui keanekaragaman jenis tumbuhan berguna dan pemanfaatannya oleh masyarakat lokal di Bandar Pusaka, Kabupaten Aceh Tamiang, Indonesia. Metode: Kajian etnobotani dilakukan pada sepuluh desa di kecamatan Banar Pusaka, meliputi Desa Pengidam, Bengkelang, Batu Bedulang, Babo, Perupuk, Serba, Pantai Cempa, Rantau Bintang, Aras Sembilan, dan Blang Kandis. Survei etnobotani dilakukan pada Juli hingga Agustus 2023 dan melibatkan 306 responden yang dipilih secara acak. Investigasi etnobotani menggunakan kuesioner semi-terstruktur untuk mengumpulkan informasi tentang pengetahuan tradisional tentang tumbuhan berguna. Spesimen tumbuhan dikumpulkan dan diidentifikasi di Universitas Samudra. Hasil: Sebanyak 2.088 individu tumbuhan yang mewakili 276 jenis dan 81 suku tumbuhan telad ditemukan di lokasi penelitian. Berkaitan dengan frekuensi kutipan, 121 taksa telah dikutip oleh 75% atau lebih dari orang yang diwawancarai, dan 9 taksa sangat jarang dikutip. Musa x paradisiaca L., Mangifera indica L., Cocos nucifera L., Durio zibethinus L., Garcinia mangostana L., Curcuma longa L., Kaempferia galanga L., Zingiber officinale Roscoe, Annona muricata L., dan Ananas comosus (L .) Merr. merupakan sepuluh tumbuhan berguna yang paling banyak dikutip di lokasi studi. Sebanyak 14 kategori kegunaan tumbuhan telah diiidentifikasi dengan kategori yang paling banyak untuk obat (111 spesies), diikuti dengan tanaman hias (100), makanan (96), pakan ternak (30), ritual (14), minuman (13), bahan bangunan (11), kayu bakar (9), alat pertanian, pagar, dan herbisida (masing-masing 6), kerajinan tangan (4), dan tanaman peneduh (2). Pengetahuan masyarakat lokal mengenai tanaman bermanfaat secara signifikan berhubungan dengan desa, kelompok umur, dan tingkat pendidikan. Kesimpulan: Kecamatan Bandar Pusaka memiliki beragam jenis tumbuhan bermanfaat, namun hanya sebagian kecil yang dimanfaatkan oleh masyarakat setempat, khususnya untuk tumbuhan liar. Promosi dan domestikasi tumbuhan berguna harus menjadi perhatian utama di Kecamatan Bandar Pusaka agar dapat memanfaatkan nilai gizi dan potensi nilai ekonominya. Selain itu, meningkatkan kemampuan dan keterampilan masyarakat lokal dalam mengenali, mengumpulkan, dan menyiapkan berbagai jenis tumbuhan berguna sangatlah penting, karena selain meningkatkan pendapatan rumah tangga, aktivitas ini juga dapat berkontribusi terhadap pelestarian keanekaragaman hayati dan pengetahuan tradisional. Kata kunci: Biodiversitas; jasa lingkungan; pengetahuan asli; Aceh Tamiang